PRODUCTION, ISOLATION, IMMOBILIZATION AND APPLICATION OF GLUCOAMYLASE FROM RHIZOPUS ORYZAE - A.T. Karossi; L.Z. Udin (Jurnal Kimia Terapan Indonesia, 2009)
Experiments were conducted to find optimum medium and process conditions based on shake-flask and laboratory fermentor scales to anticipate industrial scale for the production of glucoamylase. Membrane filtration and ammonium sulfate precipitation were tested for the enzyme concentration and isolation respectively. The glucoamylase enzyme properties were determined and preference to various starch substrates were checked. Immobilization within commercial agar and alginate were done and their shelf-life were observed. The application of free glucoamylase in saccharification of the various starches were also investigated after being liquefied with commercial alpha-amylase.Keywords : rhizopus oryzae, glucoamylase, isolation, immobilization.